PELAKSANAAN TUGAS POKOK DAN FUNGSI BADAN NARKOTIKA NASIONAL KOTA PEKANBARU DALAM PENCEGAHAN PENGGUNAAN NARKOTIKA - Hendra, Pebri Pelita; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of BNN Pekanbaru City in the prevention of drug use. This study aims to determine the tasks and functions BNN Pekanbaru City and the factors that affect the performance of duties in the prevention of drug use in the city of Pekanbaru. This study used a descriptive approach with qualitative methods. Source data from the primary data obtained through interviews with key informants, including the head of BNN, BNN and Employees in the Office of the city of Pekanbaru. The results showed the duties and functions of the city of Pekanbaru BNN influenced by human resources, systems used and community participation. Factors affecting the implementation of human resources is a task that is still lacking with wide area coverage and factor less community participation.Keywords: Management Functions, Organization, Implementation principal tasks and functions.